The holomorph of Arthrinium setariae sp. nov. (Apiosporaceae, Xylariales) from China - Jiang, Ning; Tian, Cheng-Ming (Phytotaxa, 2021)
Arthrinium is a widely distributed genus occurring on various hosts and substrates. Members of Arthrinium were distinguished based on the phylogeny of combined internal transcribed spacers (ITS), translation elongation factor 1-alpha gene (tef1), and beta-tubulin gene (tub2). In the present study, a specimen of obvious stromata on Setaria viridis was collected in Beijing Forestry University. Identification based on characters of sexual morph on Setaria viridis culms, asexual morph from manual media, and phylogeny indicated that it is different from any known species. Hence, we proposed a new species for this taxon named Arthrinium setariae. Arthrinium setariae has much larger conidia than its phylogenetically close species, A. jiangxiense, and represented the first record of Arthrinium inhabiting the host genus, Setaria.